Some properties of the positive boolean dependencies in the database model of block form - Tuyen, Tran Minh; Thang, Trinh Dinh; Huy, Nguyen Xuan (Journal of Computer Science and Cybernetics, 2015)
The report proposes the concept of positive boolean dependency in the database model of block form, proving equivalent theorem of three derived types, necessary and sufficient criteria of the derived type, the member problem... In addition, some properties related to this concept in the case of block r degenerated into relation are also expressed and demonstrated here.